Association of TAS2R38 variants with sweet food intake in children aged 1–6 years. (1st December 2016) - Pawellek, Ingrid; Grote, Veit; Rzehak, Peter; Xhonneux, Annick; Verduci, Elvira; Stolarczyk, Anna; Closa-Monasterolo, Ricardo; Reischl, Eva; Koletzko, Berthold; ,
Abstract: We aimed at studying whether genetic variants of the TAS2R38 gene are associated with energy intake from sweet tasting foods, total energy and macronutrient intake and body weight in children. Children (n = 691) from five European countries were genotyped for the first variant site rs713598 of the TAS2R38 bitter receptor gene. Three-day dietary records were obtained yearly from one to six years of age. Foods were categorized in sweet and non-sweet-tasting. Mixed models were used to describe group differences in food and nutrient intake and BMI z-score over time. TAS2R38 genotype was related to energy intake from sweet tasting foods: Children with PP and PA genotype consumed an average 83 kJ/d (95% CI 21 to 146; p = 0.009) more sweet tasting foods than children with AA genotype and a mean 56 kJ/d (95% CI 15 to 98; p = 0.007) more energy from energy dense sweet products. Intake of sweet tasting foods was lower in girls than boys and differed between countries. TAS2R38 genotype was not associated with the intake of energy, macronutrients, sugar, single food groups and BMI z-score. Despite many other factors influencing food preference and intake in children, actual intake of sweet food items is associated with TAS2R38 genotype. Children with PP or PA genotype consume more (energy dense) sweet tasting foods.